A distopia The Handmaid's Tale: um alinhavo entre afeto, identificação, memória e feminismo - Alves, Ana Carolina Tardivo (2021)
Given the fact that the costumes of The Handmaid's Tale series (Bruce Miller, 2017-) have become a powerful symbol in many protests around gender inequality and women rights, this research investigates how the narrative genre through which the series builds its plot - a dystopian scientific - engages viewers; identifying and analyzing the elements of audiovisual materiality that invite fans to be affected and to experiment this universe in a similar way to the protagonist. In another sense, this research proceeds by connecting the social context of women, the feminist movement, the use of social platforms and The Handmaid's Tale series, seeking to understand how these phenomena are capable of transforming collective and social memory. By this gaze, it was possible to perceive how the way in which women and the totalitarian universe are represented in the series causes identification in viewers. This is the link that forms the connection of the fictional narrative of THT with the social and political context in which the series is consumed, thus expanding its meaning to the reality of public and political spaces.